2003
DOI: 10.1186/cc2333
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base status of critically ill patients with acute renal failure: analysis based on Stewart–Figge methodology

Abstract: Correspondence: Rinaldo Bellomo, rinaldo.bellomo@armc.org.au AG = anion gap; APACHE = Acute Physiology and Chronic Health Evaluation; ARF = acute renal failure; ICU = intensive care unit; SIDa = apparent strong ion difference; SIDe = effective strong ion difference. AbstractIntroduction The aim of the present study is to understand the nature of acid-base disorders in critically ill patients with acute renal failure (ARF) using the biophysical principles described by Stewart and Figge. A retrospective controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In the past there have been studies which demonstrated that kidney injury can influence morbidity and mortality directly by causing water and salt retention leading to hyperkalemia, acidosis [1718]and fluid overload. However, AKI has been associated with increased insulin resistance and protein breakdown that can lead to immune system dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In the past there have been studies which demonstrated that kidney injury can influence morbidity and mortality directly by causing water and salt retention leading to hyperkalemia, acidosis [1718]and fluid overload. However, AKI has been associated with increased insulin resistance and protein breakdown that can lead to immune system dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary results of our group showed that sequential analysis of some urinary biochemical parameters has a potential role in detect AKI even before increases in creatinine [14,15]. In addition, a physicochemical acid–base analysis of blood [16] and urine [17,18] has also been previously used to describe some of the alterations that occur when renal function is impaired. However, these studies were limited to patients with established AKI: none has focused on a sequential evaluation of these physicochemical parameters in the course of AKI, including the days preceding AKI diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate renal H ϩ secretion caused, for example, by mutations to acid-base transporters (1)(2)(3)(4) or carbonic anhydrases (5), or by renal failure (6,7), can lead to a life-threatening decrease in blood pH. Moreover, to maintain a stable blood pH, the kidney must appropriately increase H ϩ secretion in response to metabolic acidosis (a decrease in blood pH caused by a decrease in [HCO 3 Ϫ ] at a fixed CO 2 ) or to respiratory acidosis.…”
mentioning
confidence: 99%